Population Dynamics and Life Table Studies of Conocephalus maculatus in Chennai District of Tamil Nadu, India - Senthilkumar, N.; Sanjayan, K. P. (Indian Forester, 2006)
Population dynamics and life tables of Conocephalus maculatus were studied by field census data and laboratory rearing. Five differents localities, representing four habitat types such as forestland (Guindy Reserve Forest), agricultural crop field (Kanchipuram), grasslands (Nungambakkam and Kodambakkam) and wasteland (Chenglepet) were selected as study sites. Adults as well as nymphs were recorded throughout the year in all habitats except at Chenglepet (wasteland) where they were observed only during rainy months from September to November. In general, adult populations showed a slightly decreasing trend in abundance from January to June each year, with the population building up from August and attaining a peak in October. More or less similar trend was observed in all the three years of study. Laboratory breeding was done at a mean temperature of 23Â°C and a relative humidity of 60% and baby corn (an immature flowering part of Zea mays) as food material. Pieces of Panicum maximum were provided for oviposition. Life tables based on age specific survival and fecundity of mated females, were constructed following the standard procedure. The results from the laboratory observations revealed that 49% mortality was prevalent at the egg stage itself. Survival of C.maculatus decreased with increase in the age. The total generation mortality in laboratory studies is less when compared to the wild population because in the laboratory conditions they are devoid of natural enemies and are not affected by extreme weather conditions. The proportion of female births obtained in the next generation was very low. This is because of the high mortality in the early nymphal stages. The net reproductive rate for the next generation was lowered considerably. In sum this study indicates that the temperature and rainfall play a vital role in the population dynamics of C.maculatus. The differences in the population dynamics of C. maculatus in different habitats may be due to their local physical environment including availability of hosts.